Effectiveness of Cognitive Conflict-Based Teaching Material Integrated with Augmented Reality in Improving Students’ Conceptual Understanding and Self-Efficacy on Light Waves - Intan Ayu Tresna; Fatni Mufit; Ratnawulan Ratnawulan; Selma Riyasni (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2026)
Effective physics learning should enable students to develop sound conceptual understanding and strong self-efficacy to solve scientific problems. Physics learning on light waves remains challenging due to students’ low conceptual understanding, misconceptions, and low self-efficacy caused by abstract concepts and teacher-centered instruction. These challenges highlight the need for innovative teaching materials. This study aimed to investigate the effectiveness of Augmented Reality (AR)-integrated cognitive conflict-based teaching materials in improving students’ conceptual understanding and self-efficacy. A quasi-experimental study employing a nonequivalent pretest–posttest control group design was conducted with 36 experimental and 33 control class students at SMA Negeri 1 Batusangkar. Data from a validated four-tier diagnostic test and self-efficacy questionnaire were analyzed using descriptive statistics, Mann–Whitney U, and Independent Sample t-tests. Results showed the experimental class's correct understanding increased from 26% to 80%, while misconceptions decreased from 40% to 8%. Statistical analysis revealed significant differences in conceptual understanding (p < .001) and self-efficacy (p < .001) between classes. These findings demonstrate that AR-integrated cognitive conflict-based materials effectively enhance both cognitive and affective outcomes, serving as an impactful instructional alternative to overcome learning difficulties in abstract physics topics.